Combination chemotherapy with bevacizumab and S-1 for elderly patients with metastatic colorectal cancer (BASIC trial). Issue 8 (May 2015) - Yoshida, M.; Muro, K.; Tsuji, A.; Hamamoto, Y.; Yoshino, T.; Yoshida, K.; Shirao, K.; Miyata, Y.; Takahari, D.; Takahashi, T.; Ohtsu, A.
Abstract Background Chemotherapeutic regimens for elderly patients with metastatic colorectal cancer (mCRC), such as bevacizumab combined with 5-fluorouracil (5-FU) and leucovorin, often exclude oxaliplatin and irinotecan owing to the risk of toxicity. However, treatment with infusional 5-fluorouracil and leucovorin requires percutaneous port-catheter placement and other precautions, causing unnecessary stress for patients as well as healthcare workers. Methods We conducted a phase II study to evaluate the efficacy and safety of bevacizumab plus S-1 in elderly patients with previously untreated mCRC. Bevacizumab was given intravenously every two weeks, and S-1 was administered orally on days 1–28 of a 42-day cycle. The primary end-point was progression-free survival (PFS). The secondary end-points were time to treatment failure, response rate (RR), overall survival (OS), treatment completion status and safety. Results From October 2007 through March 2010, 56 patients were enroled. The median PFS was 9.9 months, the median OS was 25.0 months, and the RR was 57%. The main adverse events of grade 3 or higher were hypertension (11%), diarrhoea (9%) and neutropenia (7%). Conclusion Our results suggest that combination chemotherapy with S-1 and bevacizumab can be administered safely and continuously on an outpatient basis and is therapeutically effective in elderly patients with mCRC.